PERBANDINGAN EFEKTIVITAS METODE DISKUSI KELOMPOK DENGAN MEDIA FLIP CHART DAN DEMONSTRASI DENGAN MEDIA MANEKEN DALAM PENINGKATAN PENGETAHUAN, SIKAP DAN PRAKTEK SADARI - Zulkarnain, Elfian; Lutviatin, Novia; Qur’ani, Nur Fatin (IKESMA, 2009)
In Indonesia, breast cancer represent as second cancer at most suffered by women after uterus cancer. Based on data that collected in Kanker Dharmais hospital, about 100 of case per year, most of (86%) patient come at advanced stadium. Though, progressively known its existence early, ever greater can be healed with more handling, precisely. In fact, possibility incidence bump at breast can be known by Breast-Self-Examination. Breast cancer can be prevented at moment that the women entering teen-age. Education of cancer in school and extramural for student and adolescent described in a trilateral preventive coordination of cancer which released in guiding execution of primary preventive Committee of National Preventing on Cancer. The purpose of this research were: analyzing difference the effectiveness of discussion on group with media flip chart and demonstrate with media of maneken methods. This research represent as quasi experiment with non equivalent group design, 90 samples of schoolgirl divided become 3 groups that is experiment group I counted 30 schoolgirl given health education by discussion on group with flip chart, experiment group II counted 30 schoolgirl given health education by demonstrate with maneken, and group III do not get health education (control group). Result of research show: ed there was difference which that significant on level of knowledge, attitude and practice among experiment and control group. Besides, there was difference level of knowledge, attitude and practice among before and after treatment at experiment group I, significantly. At group II, there difference on level of knowledge and practice, significantly, while for attitude, there is a difference which among before and after treatment. Based on data on analysis, known that there no difference of effectiveness level of attitude and practice among experiment group I and experiment group II, except on the of knowledge. Keywords: Health Education; Breast-Self-Examination